Epithelial-Macrophage Crosstalk Initiates Sterile Inflammation in Embryonic Skin - Bhattacharjee, Oindrila; Ayyangar, Uttkarsh; Kurbet, Ambika S.; Lakshmanan, Vairavan; Palakodeti, Dasaradhi; Ginhoux, Florent; Raghavan, Srikala (Frontiers in Immunology, 2021)
TMacrophages are highly responsive to the environment cues and are the primary responders to tissue stress and damage. While much is known about the role of macrophages during inflammatory disease progression; the initial series of events that set up the inflammation remains less understood. In this study, we use next generation sequencing (NGS) of embryonic skin macrophages and the niche cells - skin epithelia and stroma in the epidermis specific knockout of integrin beta 1 (Itgβ1) model to uncover specific roles of each cell type and identify how these cell types communicate to initiate the sterile inflammatory response. We demonstrate that while the embryonic skin fibroblasts in the Itgβ1 knockout skin are relatively inactive, the keratinocytes and macrophages are the critical responders to the sterile inflammatory cues. The epidermis expresses damage associated molecular patterns (DAMPs), stress response genes, pro-inflammatory cytokines, and chemokines that aid in eliciting the inflammatory response. The macrophages, in-turn, respond by acquiring enhanced M2-like characteristics expressing ECM remodelling and matrisome signatures that exacerbate the basement membrane disruption. Depletion of macrophages by blocking the CSF1 receptor (CSF1R) results in improved basement membrane integrity and reduced ECM remodeling activity in the KO skin. Further, blocking the skin inflammation with celecoxib reveals that the acquired fate of macrophages in the KO skin is dependent on its interaction with the epidermal compartment through COX2 dependent cytokine production. Taken together, our study highlights a critical crosstalk between the epithelia and the dermal macrophages that shapes macrophage fate and initiates sterile inflammation in the skin. The insights gained from our study can be extrapolated to other inflammatory disorders to understand the early events that set up the disease.